The ALMA Phasing System: A Beamforming Capability for Ultra-high-resolution Science at (Sub)Millimeter Wavelengths. (13th December 2017) - Matthews, L. D.; Crew, G. B.; Doeleman, S. S.; Lacasse, R.; Saez, A. F.; Alef, W.; Akiyama, K.; Amestica, R.; Anderson, J. M.; Barkats, D. A.; Baudry, A.; Broguière, D.; et al.
Abstract: The Atacama Millimeter/submillimeter Array (ALMA) Phasing Project (APP) has developed and deployed the hardware and software necessary to coherently sum the signals of individual ALMA antennas and record the aggregate sum in Very Long Baseline Interferometry (VLBI) Data Exchange Format. These beamforming capabilities allow the ALMA array to collectively function as the equivalent of a single large aperture and participate in global VLBI arrays. The inclusion of phased ALMA in current VLBI networks operating at (sub)millimeter wavelengths provides an order of magnitude improvement in sensitivity, as well as enhancements in u – v coverage and north–south angular resolution. The availability of a phased ALMA enables a wide range of new ultra-high angular resolution science applications, including the resolution of supermassive black holes on event horizon scales and studies of the launch and collimation of astrophysical jets. It also provides a high-sensitivity aperture that may be used for investigations such as pulsar searches at high frequencies. This paper provides an overview of the ALMA Phasing System design, implementation, and performance characteristics.